STRATEGI PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENINGKATKAN SIKAP TOLERANSI SISWA DI LINGKUNGAN SEKOLAH SMA SRIJAYA NEGARA - Agra Alfareza; Emil El Faisal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of Pancasila education learning strategies in improving students' tolerance attitudes at SMA Srijaya Negara Palembang. Using a qualitative approach with descriptive methods, the research involved 5 informants consisting of 3 grade X students, 1 Pancasila education teacher, and 1 homeroom teacher. Data collection techniques were conducted through participatory observation, in-depth interviews, and documentation. Data analysis used an interactive analysis model with stages of data reduction, data presentation, and conclusion drawing. The research results show that Pancasila education learning strategies have been effective in improving students' tolerance attitudes with a success rate of 88.89% categorized as "excellent". The implementation of tolerance is reflected in three main indicators: appreciating differences, accepting diversity, and respecting others' rights. Various learning methods such as group discussions, diversity festivals, and collaborative activities have proven capable of changing students' paradigm about diversity into wealth that strengthens national unity.